Analysis of Consumers' Perception on Purchase Decisions of Takeaway Coffee Drinks in Yogyakarta - Fauzia Adni Alita; Dyah Ismoyowati; Wagiman Kastawiyana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
This study aimed to determine and analyze the effect of brand image, product, price perception, and preference on purchase decisions of takeaway coffee. The research analyzed variables that most influence purchase decisions of coffee drink takeaway in Yogyakarta and the effect of each independent variable. Data were collected using an online questionnaire from individuals who have purchased takeaway coffee drinks in Yogyakarta more than once. The sample size was 100 respondents, selected using non-probability sampling techniques with the purposive sampling method. The other process was analyzing data by employing a multiple regression approach. The results showed that brand image and product positively affected purchasing decisions with t-count values of 2.340 and 2.715 and significant levels of 0.008 and 0.006, respectively. Price perception reversely influences purchasing decisions, with a t-value of 1.626 and a significance level of 0.107. Preference positively affected purchasing decisions with a t-value of 5.605 and a significance level 0,000. Furthermore, brand image, product, price perception, and preference positively affected purchasing decisions, with an F value of 65.334 and a significance level 0.000. (6) The magnitude of brand image, product, price perception, and perception of takeaway coffee drinks on purchasing decisions (adjusted R 2 ) is 0.504. Considering these results, the regression equation obtained was Y = -0,177 + 0,293X1 + 0,273X2 + 0,320X3 + 5,550D1 + e.